1998
DOI: 10.1128/jb.180.1.41-45.1998
|View full text |Cite
|
Sign up to set email alerts
|

All Seven comG Open Reading Frames Are Required for DNA Binding during Transformation of Competent Bacillus subtilis

Abstract: The seven proteins encoded by the comG operon ofBacillus subtilis exhibit similarity to gene products required for the assembly of type 4 pili and for the secretion of certain proteins in gram-negative bacteria. Although polar transposon insertions in comG result in the loss of transformability and in the failure of cells grown through the competence regimen to bind DNA, it was not known whether the ComG proteins are all required for competence. We have constructed strains missing each of these proteins indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 25 publications
1
64
0
1
Order By: Relevance
“…Recently, we have found that ComEA is a DNA binding protein, with higher affinity for double-stranded than for single-stranded DNA (Provvedi and Dubnau, 1998). Mutants deficient in any of the ComG proteins also fail to bind DNA (Chung and Dubnau, 1998), although ComEA is still present in such mutants (Provvedi and Dubnau, 1998). In vitro experiments designed to detect DNA binding to the ComG proteins have yielded uniformly negative results (Provvedi and Dubnau, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have found that ComEA is a DNA binding protein, with higher affinity for double-stranded than for single-stranded DNA (Provvedi and Dubnau, 1998). Mutants deficient in any of the ComG proteins also fail to bind DNA (Chung and Dubnau, 1998), although ComEA is still present in such mutants (Provvedi and Dubnau, 1998). In vitro experiments designed to detect DNA binding to the ComG proteins have yielded uniformly negative results (Provvedi and Dubnau, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Among the competence proteins with orthologues in the other competence systems are those encoded by the B. subtilis comG operon (Albano et al, 1989). This operon specifies seven gene products that are individually required for the binding of DNA to the competent cell Breitling and Dubnau, 1990;Chung and Dubnau, 1998). The ComG proteins belong to several families, each with members required for the assembly of pili and for the secretion of proteins across the outer membranes of certain Gram-negative bacteria, in addition to those needed for competence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we determined how long it took, after initiation of ComK expression, for competence to reach the ability to take up extracellular DNA. As a marker for functional competence, we utilized the localization of the membrane protein ComGA to the cell pole, as part of the ATP-dependent complex required for uptake of extracellular DNA (Chung and Dubnau, 1998;Hahn et al, 2005). Furthermore, ComGA localization has also been suggested to participate in the blocking of chromosome replication during competence (Haijema et al, 2001).…”
Section: Da Cells Lack Sufficient Time To Develop Functional Competencementioning
confidence: 99%
“…Competence development is initiated when a threshold level of ComK is reached and comK auto-activation is triggered (Maamar and Dubnau 2005;Smits et al 2005b). ComK in turn activates the expression of the comG operon, which encodes factors required for the uptake of exogenous DNA from the environment (Chung and Dubnau 1998). Previously, it was shown that the promoter of the comG operon fused to the gfp gene is a good reporter to identify cells that have initiated competence development (Smits et al 2005b).…”
Section: Competence and Sporulation Are Sequential Processesmentioning
confidence: 99%